KAJIAN UNIT PENANGKAPAN PURSE SEINE DI PELABUHAN PERIKANAN SAMUDERA BELAWAN (Catching Unit Studies of Purse Seine in Ocean Fishing Port of Belawan) - Fitria Ismy; Budi Utomo; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Indonesia is rich in fishery resources, but currently most exploited , one of them with the use of fishing gear in the water . For that a study has been carried out in the ocean fishing port of Belawan in July-September 2013, based on the statistical data of the ocean fishing port of Belawan and observing the purse seine and how to use it by doing an interview with purse seine fishermen . The use of purse seine fishing gear in Belawan is the highest compared to the four other types of fishing gear, to the author wants to see a business analysis of purse seine fishing gear . The method used was cluster sampling, sampling of primary data with formulas and Morgan Krejcek test samples taken 381 test samples totaling the number of 5000 population. Secondary data obtained from ocean fishing port of Belawan. Analysis of the data to calculate the catch per unit effort ( CPUE ) and business analysis. The result shows that the use of purse seine vessels is one that does not damage the ocean because of its use that much a few miles towards the sea and do not damage fish habitats. The analysis also shows that the using of purse seine fishing also more profit, the catching fishes are type of pelagic fish and do not too excessive.Key words : fishery resources, ocean fishing port of Belawan, Purse Seine.